2013
DOI: 10.2308/bria-50624
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Language Use in Accounting Narratives and Their Impact on Investment-Related Judgments and Decisions

Abstract: Recent research has examined the role of accounting narratives on investors' judgments and decisions. This study extends this line of inquiry by examining the effects of language categories on investors' judgments and decisions—the notion that narratives written with different predicates (verbs versus adjectives/nouns) will have a differential effect on investors. We use a language classification system, the Linguistic Category Model (LCM), to identify linguistic categories that vary on the dimension of abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 61 publications
1
49
0
2
Order By: Relevance
“…Investors from Eastern cultures, such as China, have a preference for and familiarity with concrete language, based on the prevalence of its use in these cultures. Therefore, while the U.S. investors in Riley et al () made more favorable investment judgments of a company when a negatively framed narrative was written with nouns/adjectives, the Chinese investors made more favorable investment judgments when that same negatively framed narrative was written using more verbs. Managers should be aware that the culture of their audience is going to influence how the narrative influences their judgments.…”
Section: Abstract Versus Concrete Languagementioning
confidence: 93%
See 3 more Smart Citations
“…Investors from Eastern cultures, such as China, have a preference for and familiarity with concrete language, based on the prevalence of its use in these cultures. Therefore, while the U.S. investors in Riley et al () made more favorable investment judgments of a company when a negatively framed narrative was written with nouns/adjectives, the Chinese investors made more favorable investment judgments when that same negatively framed narrative was written using more verbs. Managers should be aware that the culture of their audience is going to influence how the narrative influences their judgments.…”
Section: Abstract Versus Concrete Languagementioning
confidence: 93%
“…The takeaway for managers seems to be that if they have positive news to convey, they should write with more verbs; however, if they have negative news to convey, they are wise to do so using more nouns/adjectives, as investors will be less likely to punish the firm for this news. However, in an extension to Riley et al (2014), Yen, Riley, and Liao (2014) found the results only hold for investors from Western cultures, such as the United States. Investors from Eastern cultures, such as China, have a preference for and familiarity with concrete language, based on the prevalence of its use in these cultures.…”
Section: Abstract Versus Concrete Languagementioning
confidence: 99%
See 2 more Smart Citations
“…Davis et al (2011) analyze approximately 23,000 earning press releases using a measure of managers' net optimistic language and conclude that the measure is positively associated with future firm ROA. Finally, Riley et al (2014) demonstrates that positive (negative) financial information is associated with more concrete (abstract) language used in earnings press releases.…”
Section: The Accounting Lexiconmentioning
confidence: 99%